Improving health worker performance of abortion services: an assessment of post-training support to providers in India, Nepal and Nigeria - Janie Benson; Joan Healy; Sally Dijkerman; Kathryn Andersen (BMC, 2017)
Abstract Background Health worker performance has been the focus of numerous interventions and evaluation studies in low- and middle-income countries. Few have examined changes in individual provider performance with an intervention encompassing post-training support contacts to improve their clinical practice and resolve programmatic problems. This paper reports the results of an intervention with 3471 abortion providers in India, Nepal and Nigeria. Methods Following abortion care training, providers received in-person visits and virtual contacts by a clinical and programmatic support team for a 12-month period, designed to address their individual practice issues. The intervention also included technical assistance to and upgrades in facilities where the providers worked. Quantitative measures to assess provider performance were established, including: 1) Increase in service provision; 2) Consistent service provision; 3) Provision of high quality of care through use of World Health Organization-recommended uterine evacuation technologies, management of pain and provision of post-abortion contraception; and 4) Post-abortion contraception method mix. Descriptive univariate analysis was conducted, followed by examination of the bivariate relationships between all independent variables and the four dependent performance outcome variables by calculating unadjusted odds ratios, by country and overall. Finally, multivariate logistic regression was performed for each outcome. Results Providers received an average of 5.7 contacts. Sixty-two percent and 46% of providers met measures for consistent service provision and quality of care, respectively. Fewer providers achieved an increased number of services (24%). Forty-six percent provided an appropriate postabortion contraceptive mix to clients. Most providers met the quality components for use of WHO-recommended abortion methods and provision of pain management. Factors significantly associated with achievement of all measures were providers working in sites offering community outreach and those trained in intervention year two. The number of in-person contacts was significantly associated with achievement of three of four measures. Conclusion Post-training support holds promise for strengthening health worker performance. Further research is needed to compare this intervention with other approaches and assess how post-training contacts could be incorporated into current health system supervision.